2021
DOI: 10.21608/jpp.2021.98337.1065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growing Area on Yield Traits, Fiber and Yarn Properties in Egyptian Cotton Genotypes by Using Biofertilizer Inoculation, Vermicompost and Algae Extract. تأثير منطقة الزراعة على صفات المحْصول وصفات جوُدة التيلة والغزل لبعْض التراکيب الوراثية فى القُطن المصْرى بإستخدام التلقيح الحيوى والفيرم کُمبوست ومُستخْلص الطحالب

Abstract: These experiments were conducted to study the response of some Egyptian cotton, Giza 96 (extralong stable) and Giza Giza 96 (extra-long stable)varieties and its yield characteristic, lint percentage, fiber and yarn properties when using bio-fertilizers such as vermicompost, Bacteria bacteria inoculums (Bacillus polymxa, Bacillus megaterium and Bacillus circulans) and algae extract under different growing area, Sakha region (clay soil) and El-Nubaria region (calcareous soil).Concerning the effect of different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…3 ). Our results are in agreement with Ahmed et al 64 who found that the content of chlorophylls a and b and carotenoids in cotton leaves was significantly improved by algal extract as compared to the control. The application of U. rigida extract to wheat plants under salt stress conditions led to a significant increase in Total Chl (T-Chl), Chl-a, and Chl-b 65 , 78 .…”
Section: Resultssupporting
confidence: 93%
“…3 ). Our results are in agreement with Ahmed et al 64 who found that the content of chlorophylls a and b and carotenoids in cotton leaves was significantly improved by algal extract as compared to the control. The application of U. rigida extract to wheat plants under salt stress conditions led to a significant increase in Total Chl (T-Chl), Chl-a, and Chl-b 65 , 78 .…”
Section: Resultssupporting
confidence: 93%